Labor Augmentation in Primigravida: A Comparative Evaluation of Drotaverine and Tramadol: Labor Augmentation in Primigravida - Tasneem, Maria; Makhdoom, Benish Fatima; Shahwar, Durre (Pakistan Journal of Health Sciences, 2025)
Prolonged labor increases maternal and fetal risks. Pharmacological agents such as Drotaverine hydrochloride and Tramadol have been utilized to shorten the duration of labor by facilitating cervical dilation and uterine activity. However, comparative evidence regarding their efficacy and safety remains limited. Objective: To compare the effectiveness of Drotaverine hydrochloride and Tramadol in reducing the duration of active labor in primigravida women, and to assess associated maternal and neonatal outcomes. Methods: This quasi-experimental study was conducted at the Department of Obstetrics and Gynecology, Niazi Medical and Dental College, Sargodha. A total of 146 primigravida women in active labor were divided into two groups (n=73 each) using non-probability consecutive sampling. Group A received intravenous Drotaverine hydrochloride (40 mg every 2 hours, up to 3 doses), while Group B received intramuscular Tramadol (100 mg, single dose). Duration of labor stages, cervical dilation rate, maternal side effects, and neonatal outcomes were recorded and analyzed using SPSS version 20.0. A p-value ≤ 0.05 was considered significant. Results: The first stage of labor was significantly shorter in the Drotaverine group (208.7 ± 38.5 min) compared to the Tramadol group (228.9 ± 42.3 min, p = 0.001). Drotaverine also showed a significantly higher cervical dilation rate and fewer maternal side effects such as nausea and dizziness. Neonatal outcomes were comparable between both groups. Conclusion: Drotaverine hydrochloride was more effective than Tramadol in shortening the first stage of labor with fewer maternal side effects, making it a preferable agent in primigravida labor management.